Reorienting Infrastructure Development in Panggang Lake Area: Towards Agritourism - Clarrio Dimassetya Jaya (The Indonesian Journal of Planning and Development, 2020)
Tourism escalates the economics in many undeveloped regions. It is more effective than others because the industry creates substantial multiplier effects and stimulates the growth of the local economy. Tourism provides many potential livelihoods to build up the local community's incomes. Global trends influence the growth of tourism. Nowadays, the worlds prefer to experience high-value production of unique commodities than massive tourism product. In Panggang Lake Area, swamp buffalo personify the locality phenomenon. The buffalos successfully adapt to live in a wet swamp, and even they are a good swimmer. Since Banjar Sultanate civilization, the community farms swamp buffalos in Panggang Lake Area. The unique ability of swamp buffalo builds a potency of tourism attraction. For those reasons, The North Upstream Regency plans Panggang Lake Area to be a tourist destination. However, as the germ-plasma sources, the tourism development in Panggang Lake Area should cooperate on some local wisdom. The local community works as a buffalo farmer so that the tourism development would make several changes in the daily life structures. This study aims to find out the most fitted concept of infrastructure development towards agritourism. The importance of socio-economic and environmental factors analyzed study participants' preferences for evaluating the appropriateness of tourism development in Panggang Lake Area. The study concludes the concept of watching tourism to be the more appropriate concept of agritourism infrastructure development in Panggang Lake Area.